Do-it-yourself methodology for calorimeter construction based in Arduino data acquisition device for introductory chemical laboratories (2019)
Many experimental thermochemical laboratories require monitoring temperatures during a reaction or physical procedure. Nowadays, there are many alternatives to fulfill this requirement; however, they are expensive for basic scholars and first-year undergraduates. In this paper, we describe an inexpensive and useful data acquisition device developed with the open-source Arduino software. In this work, we presented a methodology for easy calorimeter construction based in Arduino data acquisition device for introductory chemical laboratories, we used an LM35 transistor as a temperature sensor connected to an Arduino UNO microcontroller for temperature sensing and an aquarium air pump for agitation of reaction system. Besides, the hardware required for implementation is explained in detail. The device was built using the (DIY) do-it -yourself method, and the complete system had a total cost under $40. We showed details of all components for data acquisition construction. Finally, we tested the device in order to determine the exothermic dissolution heat (ΔH) for NaOH in water.